Cluster glycosides and heteroglycoclusters presented in alternative arrangements. Issue 50 (12th December 2018) - Figueredo, Andreza S.; Zamoner, Luis O.B.; Rejzek, Martin; Field, Robert A.; Carvalho, Ivone
Graphical abstract: Highlights: Tetra and hexavalent glycoclusters containingd -glucopyranose cores were synthesised. Sugars are linked in alternate arrangements through C-1, C-2, C-3 or C-6 positions. Heteroglycoclusters with non-identical ligands were also obtained. The iminosugar glycoclusters have trivalentd -glucose attached at C-1 or C-6 positions. These adducts have potential to resemble pseudooligosaccharides. Abstract: Multivalent carbohydrates, or glycoclusters, are useful tools to study glycan-lectin and glycan-enzyme recognition processes and have wide potential therapeutic applicability. Herein, we report the synthesis of novel glycoclusters presenting glucopyranose units in alternate arrangements by coupling through the C-1, C-2, C-3 or C-6 sugar positions and using tetra- and hexa-valent scaffolds for multivalent display. Coupling the appropriate azide-functionalisedd -glucopyranose units with alkynylated penta- or dipenta-erythritol central cores was accomplished via copper-catalysed azide-alkyne cycloaddition (CuAAC), yielding a panel of eight tetra- and hexa-valent glycoclusters in good yields (52–83%). This click chemistry strategy was extended to the preparation of four heteroglycoclusters using a tris(hydroxymethyl)-aminomethane (TRIS) central scaffold. One unit of either the conventional 1-deoxy-d -nojirymicin iminosugar or its' C-5 epimericl -gulo isomer, were incorporated along with threed -glucopyranose units linked through either C-1 or C-6.